The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.4274/tjod.galenos.2020.21284
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the pectineal ligament during pectopexy surgery: The relevance to the major vascular structures

Abstract: Objective: During pectopexy surgery, the prolapsed uterus or the vaginal apex is fixed to the pectineal ligament. The anatomic structures found in the lateral part of the prevesical and paravaginal space above the obturator fossa, raise the importance of the surgical steps required to prevent complications. This study was conducted to evaluate the proximity of vascular structures to the pectineal ligament. Materials and Methods: The distances between the surgical suturing area during pectopexy surgery and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…2 g). A cadaver study showed that the mean distance from the midpoint of the pectineal ligament to the external iliac vein was 1.04–1.25 cm and to the obturator canal was 3.12–3.57 cm [ 15 ]. The obturator nerve passes below the pectineal ligament and is relatively distant from the dissection plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 g). A cadaver study showed that the mean distance from the midpoint of the pectineal ligament to the external iliac vein was 1.04–1.25 cm and to the obturator canal was 3.12–3.57 cm [ 15 ]. The obturator nerve passes below the pectineal ligament and is relatively distant from the dissection plane.…”
Section: Discussionmentioning
confidence: 99%
“…A vessel that may be encountered during pectineal ligament preparation is the pubic vein, also called the corona mortis (Fig. 2 h), which is the anastomosis of the external iliac vein and obturator vein and lies on the pectineal ligament [ 15 ]. It can simply be cauterized if this vessel is impeding the mesh fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Pulatoglu et al measured the total length of the pectineal ligament -5.9±0.76 cm on the left and 6.5±1.14 cm on the right side. From the midpoint of the right pectineal ligament, the mean distance to the right CMOR was 2.37±0.63 cm and the mean distance to the left CMOR was 2.15±0.48 cm [44].…”
Section: Clinical Applications Of Aovs Acovs and Cmor In Gynecologymentioning
confidence: 89%
“…the external iliac vessels and the pubic spine [43].They reported that during Burch colposuspension stitches should be located near to the iliac vessels and 4 cm lateral to the medial insertion of the ligament, where it has its greatest thickness [43]. According to other study, the medial part of pectineal ligament close to the pubic tubercle was the thickest section and it became thinner while extending laterally [44]. In a study of 11 female unembalmed female cadavers, Kinman et al reported that the mean distance from the most lateral stitch in Cooper's pubic ligament to the obturator bundle was 25.9 ± 7.6 mm and to the external iliac vessels was 28.9 ± 9.3 mm, and in some instances, these structures were less than 15 mm away [39].…”
Section: Clinical Applications Of Aovs Acovs and Cmor In Gynecologymentioning
confidence: 97%
See 1 more Smart Citation